夏季の南極海インド洋区における有殻翼足類（Limacina spp.）の経年変化 - 西澤, 裕子; ニシザワ, ユウコ; 佐々木, 洋; ササキ, ヒロシ; 高橋, 邦夫; タカハシ, クニオ; Nishizawa, Yuko; Sasaki, Hiroshi; Takahashi, Kunio T. (国立極地研究所, 2016)
海洋酸性化がアラゴナイトの殻を形成する有殻翼足類に及ぼす影響を明らかにするため，1987 年から2008 年の夏季に，南緯55–64 度，東経110 度付近海域において日本南極地域観測隊により採取された有殻翼足類試料を用いてその現存量と殻径の経年変動を調べた．有殻翼足類（Limacina 属が優占）の殻径はほとんどが400 μm 未満で，現存量は最小2.2 ind. m－3 から最大2767.7 ind. m－3 の間で変動していた．55°S, 60°S, 64°S の3 測点付近の水深400 m 以浅においては海水pH の有意な減少は確認されなかった．また有殻翼足類の現存量においても年変動が大きく1987 年から2008 年の20 年間で有意な減少傾向を示さなかった．またそれらのサイズも有意な減少傾向は見いだせなかった．南極海における海洋酸性化は今後徐々に進行すると思われるが，有殻翼足類に対する影響はまだ顕在化していないと考えられる． Euthecosomatous pteropods with carbonate (aragonite) shells living in polar waters are thought to be very sensitive to ocean acidification resulting from increased anthropogenic CO2 uptake. To assess the impacts of ocean acidification on pteropods, we investigated pteropod abundance and shell size at three sites located between 55 and 64°S on the 110°E meridian in the Indian sector of the Southern Ocean during austral summer from 1987 to 2008 with the Japanese Antarctic Research Expedition (JARE) monitoring projects. The pteropod community was dominated by Limacina spp. with a shell size of ＜400 μm, and there was a distinct interannual variation ranging 2.2–2767.7 ind. m－3. No significant decrease in pH was detected in various water layers above 400 m depth at three sites (55°S, 60°S and 64°S) during the study period, and no marked decrease both in abundance and shell size have been observed in these waters for at least 20 years. Though ocean acidification in the Southern Ocean will be in progress, the effects on shelled pteropods are not yet evident. departmental bulletin paper